Ethical and legal implications of Sri Lanka’s guideline-based approach to assisted reproductive technologies - Abeyrathna, D. (University of Colombo, 2025)
Sri Lanka’s recent strides in assisted reproductive technologies (ART), including the formulation of ministerial guidelines and establishing its first government hospital-based sperm bank, mark a significant shift in the reproductive healthcare landscape. However, these developments have occurred without a corresponding legislative framework. Without binding laws, ART in Sri Lanka is governed solely by non-enforceable administrative guidelines, circulars, and professional discretion. This paper argues that a guideline-based approach, while useful as a transitional measure, is insufficient to uphold ethical standards, provide legal clarity, and protect the rights of all stakeholders involved in ART, particularly donors, surrogates, intended parents, and children born through these technologies. Drawing on core bioethical principles, the paper explores key ethical and legal risks arising from the absence of binding legislation, examines existing impediments to legislating on ART, and discusses ways to address these challenges. The study further engages in a comparative legal analysis with India, which transitioned from an unregulated ART market to a tightly controlled legal regime under the Surrogacy (Regulation) Act, 2021 and the Assisted Reproductive Technology (Regulation) Act, 2021. The significance of this study lies in its contribution to the emerging discourse on reproductive governance in Sri Lanka, providing critical insights at a significant moment of policy reform. Employing a qualitative legal-ethical methodology, the study integrates doctrinal analysis of Sri Lanka’s ART guidelines with normative ethical evaluation and comparative legal reasoning. The paper concludes that Sri Lanka must move beyond guidelines and adopt a rights-based, context-sensitive legal framework to ensure ethical accountability, legal certainty, and the best interests of the child.
Keywords: ART; Guideline-based approach; Donors; Surrogates; Intended parent